ESRA19-0701 Local anaesthetic (LAS) neurotoxicity after PNBS: current data - Moka, E; Makris, A; Theodoraki, K; Siafaka, I; Vadalouca, A (Regional anesthesia and pain medicine, 2019)
Strong, laboratory and clinical evidence of potential local anaesthetics (LAs) in situ neurotoxicity exists in literature. However, the relative importance of LAs toxicity to the generation of nerve injury is unknown and, data regarding the exact incidence of peripheral nerve damage, solely attributed to LAs induced direct neurotoxicity, are lacking. Interestingly, data do exist regarding percentages of nerve injury following peripheral nerve blocks (PNBs), with the overall incidence of neurological complications of any severity being low, and with studies estimating them below 3:100 (3 over a hundred) in the case of single shot blocks, and between 0.4 and 2% in the case of peripheral nerve catheters (PNCs). Most of these neurological complications are minor, transient sensory deficits, with permanent injury being very rare. Large prospective/retrospective studies, examining neurological complications in PNBs estimate that mild paraesthesias can be encountered in up to 15% of patients, with a complete spontaneous resolution of the majority of symptoms within days to weeks, and the encouraging report that in 99% of patients, symptoms resolve completely within 1 year. the reported incidence however varies considerably between studies and over time, possibly due to methods used to capture anaesthesia related neurologic complications, but according to the majority of authors, long term neurological injury is extremely rare, with the estimated incidence ranging between 0.024 and 0.04%.LAs capacity to damage neuronal cells remains unclear. Not only LAs, but multiple risk factors other than drugs themselves are involved, contributing to the risk of neurologic injury, with neurological function after a PNB being the net result of the interplay between all associated risk factors. By using the well-known triad model, the complex phenomenon of neurologic injury seems to result from a complicated interaction among host-patient factors (anatomic, biologic and comorbidities), causative agents (mechanical, ischaemic, and chemical neurotoxic insults) and environmental factors (RA tools, guidance techniques, supervision, safe practice culture). the neurologic injury may subsequently represent the result-final outcome of a chain of interactions among these risk factors. Minimization or elimination of any of the triangle’s components may potentially, in theory, interrupt the interaction and reduce the likelihood of the injury or possibly prevent it entirely. the individual risk factors present in this chain are themselves either contributory or necessary for the outcome to occur. Although we have classified the relevant risk factors for neurologic complications as being specific to the host, agent, or environment, whether each individual risk factor is just contributory or is necessary for event causation needs to be determined in the future. Hence, the safest approach appears to be identification and prevention of all potential risk factors. Many of the factors responsible for neurologic complications are non-modifiable, meaning that screening for at-risk patients is necessary.LAs have a potential for neurotoxicity (in vitro, in vivo, on cell lines and animal models and few existing human studies/clinical reports, case series or cadaveric studies). Precise pathophysiology mechanisms have not yet been fully understood, although the majority of investigators agree that in situ neurotoxicity is probably mediated by mechanisms other than VGSC and GPCR blockade. LAs can induce neurotoxicity mediated by direct pleiotropic effects on neuronal tissue ultrastructure. When when injected directly into the nerve or the adjacent tissues, LAs can cause an acute inflammatory reaction, collagen disarray or recurrent fibrosis that indirectly involves the nerve. Current histopathological studies suggest multiple types of nerve cell damage, induced by LAs, effects on nerve cells body, membrane solubilization and lysis, apoptosis, necrosis, myelin architecture disruption, wallerian degeneration, demyelination, myelin globules formation, focal myelin loss, effects on nerve fibres and axons (reduced density and loss), oedema, degeneration, schwann cell injury, electrophysiological effects (delay in axonal conductivity), effects on edge of growing nerve fibres and regenerating neurons, growth cone collapse, distal neurites destruction and fragmentation, as well as retraction of cell extension.In reference to cell ultrastructure, LAs induce a large spectrum of abnormalities. In this context, lidocaine, ropivacaine, and bupivacaine reduced the number of neurons. Moreover, incubation of the axonal compartment with 40mM lidocaine for 24 h, induced axonal degeneration with retraction of distal neuritis and fragmentation of neuritis. Additionally, in SH-SY5Y cells, 20 min treatment with 10mM lidocaine induced retraction of the cell extension. Continuous infusions of 0.5–0.75% bupivacaine for 72 h in the vicinity of the sciatic nerves of rats induced severe wallerian degeneration, with varying degrees of disruption of the normal myelin architecture, formation of myelin globules and vacuolization, and focal loss of myelin staining. Lastly, infusion of 600mM lidocaine just outside of the perineurium was associated with swollen axons, macrophage phagocytosis of degenerated tissue, and epineurial and endoneurial collagen. LAs also exert effects on neuronal microenvironment and have an impact on energy and cell metabolism, with disturbances of a diversity of cellular processes that may contribute to neuronal damage by LAs, although no single pathway is established as the clinically dominant mechanism. Even if detailed subcellular pathways of neurotoxicity have been the subject of substantial research efforts, the ‘big’ picture is still unclear.Altered Ca++ homeostasis and elevated intracellular calcium levels may play a central role. Disruption of cytoplasmic calcium signaling after LAs injection induces elevations in cytoplasmic calcium C, through plasmalemmal influx and release of calcium from intracellular stores, leading to axonal transport inhibition, membrane lysis and neuronal death from activation of kinases and altered energy metabolism.Additionally, LAs affect mitochondrial bioenergetics, and inhibit mitochondrial energy metabolism due to increased permeability of mitochondrial membrane, collapse of mitochondrial membrane potential (ΔΨ), decreased ATP synthesis (ATP depletion) and reduction of respiratory chain protein content that is localized in the inner mitochondrial membrane. Consequently, oxidative phosporylation uncoupling, mitochondrial network fragmentation and mitophagy take place, cytochrome c is released and intrinsic caspase pathway is activated, potentially resulting in nerve cells apoptosis.An important feature of LAs neurotoxicity is oxidative stress of endoplasmatic reticulum and the over production of oxygen free radicals–ROS, that can further provoke cellular damage, in terms of apoptosis (programmed cell death), or rapid necrosis especially of schwann cells.Recent studies indicate that preapoptotic enzymes such as those included the p38 MAPK pathway, might also play a central role in LAs induced neurotoxicity. the p38 MAPK phosphorylation induced by LAs, is involved in apoptosis regulation, gene expression, mitosis, DNA fragmentation, transcription and finally cell death, by an increase of CHOP (C homologous protein), which among other actions, inhibits bcl2 antiapoptotic protein, which normally counteracts cytochrome c release.Finally, another group of molecular targets that is involved in apoptosis inhibition is the Akt–ERK Pathway, playing a pivotal role in cell survival. LAs inhibit Akt and ERK, leading to reduced cell survival, and increased apoptotic activity, whereas their phosphorylation can protect form LAs induced nerve damage.In reference to dose, concentration and duration of exposure to LAs, neurotoxicity induction has been reported for several LAs, both in vitro, in various cell culture models, such as neuroblastoma, human neuronal, swan, DRG, human lymphocytes and T-lymphoma cell lines, as well as in vivo, in animal models in rats, mainly involving the sciatic nerve. According to the majority of experimental studies results, all commonly used LAs can trigger neuronal apoptosis and may decrease cell viability in clinically relevant C, or even at C well below those applied in clinical practice, whereas, higher C of LAs may cause rapid cell death and late stage apoptosis, primarily due to necrosis. LAs neurotoxicity is induced in a dose, time and concentration dependent manner, with all LAs, exerting similar rates of early apoptotic cell formation at low concentrations. In this context, probably, exposure to very high concentration for a very short time leads to a greater predominance of necrotic cell death, whereas, during long term exposure of neurons, apoptosis is possibly the major mechanism of cell death. In addition, prolonged exposure of high doses and high concentrations may finally result in – may be the cause of – permanent nerve injuries.Moreover, according to current literature, a great variability of in situ neuroapoptotic-neurotoxic properties among LAs has been suggested by several experimental studies. Interestingly, it seems that LAs neurotoxicity is strongly correlated with lipid solubility (lipophilicity-octanol buffer coefficient) and thus conduction blocking potency, either experimental or clinical. on the contrary, a low degree of correlation has been noticed between LAs neurotoxicity and pKa, protein binding or MW, whereas, neurotoxicity is independent of chemical class and structural factors (amide/ester linkage), with stereospecificity also having no influence on nerve cells cytotoxicity. as such, although S-enantiomers are indeed advantageous with regard to LAST, it seems they offer no advantage in respect to LAs’ in situ toxicity. Furthermore, a comparison of LD50 values of different LAs (in